Cracking of Two-phase Ceramics under Uniaxial Compression Deformation - SADOWSKI, Tomasz; MARSAVINA, Liviu; CRACIUN, Eduard (Engineering Transactions, 2017)
Two-phase ceramics have a non-linear and complex overall response to applied loads due to composition of two different phases with initial porosity, development of limited plasticity and internal microdefects. These microdefects cause stress concentrations and locally change the state of stress, which results in the development of mesocracks leading to macrocracks. In this article, a multiscale approach was applied to the modelling of the two-phase ceramics response under compression deformation. This allowed to include different phenomena at micro-, meso- and macro-scales.